2020
DOI: 10.1111/nmo.13954
|View full text |Cite
|
Sign up to set email alerts
|

Normative reference values for esophageal high‐resolution manometry in healthy adults: A systematic review

Abstract: Esophageal manometry has been widely used to diagnose esophageal motility disorders. 1 It is the standard diagnostic tool in nonobstructive dysphagia, as it evaluates both pressures of the lower esophageal sphincter (LES) and contractility of the esophageal body. An important advancement in the last 20 years has been the introduction of high-resolution manometry (HRM), usually defined as manometry carried out with a catheter with at least 21 channels and with sensors at 1-cm intervals. 2 HRM is swiftly replaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 55 publications
(107 reference statements)
0
9
0
Order By: Relevance
“…To minimize the remnant bolus between each swallow, which could have affected the HRIM results, we performed the test in the sitting position. Gonzalez et al 13 reported that while the IEM diagnosis was affected by changes in position to supine or sitting, that of achalasia was not significantly affected. The diagnosis of other spastic motility disorders may also be affected by the position of manometry.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…To minimize the remnant bolus between each swallow, which could have affected the HRIM results, we performed the test in the sitting position. Gonzalez et al 13 reported that while the IEM diagnosis was affected by changes in position to supine or sitting, that of achalasia was not significantly affected. The diagnosis of other spastic motility disorders may also be affected by the position of manometry.…”
Section: Discussionmentioning
confidence: 99%
“…NOD was identified according to Rome IV criteria 6 : a sensation of abnormal bolus transit through the esophageal body with a thorough exclusion of structural lesions, gastroesophageal reflux disease (GERD), and histopathology‐based esophageal motor disorders which had not been diagnosed with a major Chicago classification v3.0 motility disorder such as achalasia, esophagogastric junction outflow obstruction, diffuse esophageal spasm, jackhammer esophagus, and absent peristalsis 1,11,12 . Propensity score matching (PSM) was performed for age, sex, and body mass index (BMI) to identify eligible participants among asymptomatic controls, patients with NOD, and patients with achalasia 13,14 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“… 9 , 10 On the other hand, recent systematic reviews consistently showed that the distal contractile integral is significantly lower in the upright position than in the supine position. 10 , 11 Since at least some HRM metrics are position-dependent, it is necessary to establish and utilize posture-specific normative values in esophageal HRM. 6 , 12 - 15 Otherwise, a change of position could be included in the standard supine protocol as an adjunctive or complementary tool to enhance the diagnostic performance of esophageal HRM.…”
Section: Discussionmentioning
confidence: 99%